Ostöffnung, EU-Mitgliedschaft, Euro-Teilnahme und EU-Erweiterung: Wirtschaftliche Auswirkungen auf Österreich - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2006)
– Austria has gained economically from all integration steps taken by the European Union over the past 15 years (eastern opening, Austria's accession to the EU and its currency union, EU enlargement). With some of these steps occurring in parallel, its effects have similarly overlapped. Eastern opening since 1989 and Austria's EU membership since 1995 (and its participation in the currency union) contributed 0.5 to 1 percentage point to its economic growth and resulted in the creation of some 100,000 to 150,000 new jobs. The EU enlargement of 2004 has similarly benefiting Austria more than other EU 15 countries; growth effects for the real GDP are estimated at more than 0.2 percentage point p.a. over the next decade.
Keywords: 330; Österreich; EU; Europäische Integration; Europäische Währungsunion; EU-Erweiterung; EU-Mitgliedschaft; Eurozone; Europäische Integration; Mitgliedschaft; Österreich; Wirkungsanalyse